2009
DOI: 10.2478/v10009-009-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

The Puck Bay as an example of deep dredging unfavorably affecting the aquatic environment

Abstract: The presented study is a review of available geochemical data concerning a dredge area in the Puck Bay. It is a small, semi-closed and degraded water body on the Polish Baltic coast. In this region very deep dredging was conducted in the years 1989-95. Five dredge pits were created in the bottom of the bay. Only two of them have been geochemically investigated so far. In the deepwater parts of both the dredge pits organic matter accumulation resulted in sulfate reduction and subsequent hydrogen sulfide product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Although the work of Zhang et al (2010) showed that there was little modification in water-column oxygen, during a dredging operation in a shallow lake in China, Licursi and Gomez (2009) observed a significant increase in the oxygen demand of the water column due to resuspension of organic matter. In very anoxic sediments, where elevated concentrations of hydrogen sulfide and methane are present, dredging may promote intoxication of the organisms or a large oxygen consumption (Graca, 2009). In restricted environments, dredging may engender remineralization of nutrients, resulting in the intensification of eutrophication processes (Licursi and Gomez, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although the work of Zhang et al (2010) showed that there was little modification in water-column oxygen, during a dredging operation in a shallow lake in China, Licursi and Gomez (2009) observed a significant increase in the oxygen demand of the water column due to resuspension of organic matter. In very anoxic sediments, where elevated concentrations of hydrogen sulfide and methane are present, dredging may promote intoxication of the organisms or a large oxygen consumption (Graca, 2009). In restricted environments, dredging may engender remineralization of nutrients, resulting in the intensification of eutrophication processes (Licursi and Gomez, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Data used to assess the existing state and trends in the deep water basins, as well as information on the content of nutrients, organic matter, and geochemical and bacteriological conditions in the dredged areas have also been presented elsewhere (Bolałek 1993, Bolałek et al 1996, Graca 2004, Graca and Dudkowiak 2007, Graca 2009). Although there is some information on the gas phase in sediment from the Baltic Sea (Schmaljohan 1996, Thiessen et al 2006, Judd and Hovland 2007, there is no information on the methane content in gas bubbles.…”
Section: Introductionmentioning
confidence: 99%